Malnutrition and food insecurity projections, 2020 - Garcia, Marito (International Food Policy Research Institute, 1994)
In 1990 a total of 780 million people out of 4 billion in the developing world are living on diets that are not sufficient to maintain a healthy life, according to the Food and Agriculture Organization of the United Nations (FAO). This implies food insecurity for every fifth person in the developing world. Insufficient food consumption is one of the primary causes of malnutrition; the other is infection and poor health. Unless explicit policies to reduce the numbers of underweight are put in place, the total number of children with protein energy malnutrition will rise, and child deaths associated with malnutrition problems will continue unabated. Increase in incomes and reduction in poverty are important, but experiences in several countries indicate that even where there is no rapid improvement in incomes, malnutrition can be reduced by explicit programs and policies that aim at improving household access to food and health services and improving child care practices such as breastfeeding and proper weaning of infants. A concerted effort to follow the examples of successful countries is needed to reduce the numbers of malnourished children in the future.